Functioning of Lexical Connections in Patients with Neurodegenerative Diseases: Case Study of a Patient with Spinocerebellar Ataxia (SCA) - Gatkowska, Izabela; Jauer-Niworowska, Olga (2023)
Aim of the research: interdisciplinary description of functioning of lexical connections in a patient with spinocerebellar ataxia (SCA-type1). There is little research on lexical networks in patients with neurodegenerative diseases. Procedure: the subject was asked to give associations to 63 stimuli-lexemes. Tools used in the study: the Experimental lexical network of the Polish language, a digital recorder, an Olympus 650 DM. The Experimental lexical network was developed by Izabela Gatkowska (2017). It was created as a result of the study concerning the associations of 900 healthy Polish-speaking adults. Utterances of the subject were recorded, transcribed and compared with standard data. Results: the reactions of the subject were different from the associations presented in the Experimental lexical network. The most common verbal reactions were: creating definitions of stimuli-word meanings or making comment on them. Associations created by the subject were based on paradigmatic or syntagmatic relations. The authors explain how the specific verbal behaviour of the subject is related to the cognitive and language dysfunctions caused by the cerebellar damages. The results showed that language processing should not be regarded as separate from other cognitive functions. Verbal reactions of the subject are slightly similar to aphasic symptoms, but mostly they are related to cerebellar damage and executive disorders. The results obtained proved the validity of the connection between linguistic and psychological methods and tools in studies which concern the language behaviour of patients with neurodegenerative diseases.
Keywords: linguistics; psychology; experimental lexical network; speech-language disorders; rare neurodegenerative diseases; diagnosis; tools; methods; semantic disorders; cognitive disorders